An abnormal structure of the left ventricle. Issue 2 (27th October 2017) - Kang, Yu; Li, Zheng; He, Ben
Abstract : CLINICAL INTRODUCTION: A 36-year-old man was referred for evaluation of an abnormal left ventricular (LV) structure found incidentally on transthoracic echocardiography (TTE) (figure 1 ). He had no symptoms except for mild palpitations. There was no significant medical history. Physical examination was unremarkable. ECG showed regular sinus rhythm with ST changes in lead II, III, avF and V6 (see online supplementary file 1 ). Cardiac magnetic resonance (CMR) (figure 1 C) was performed. Treadmill exercise test did not demonstrate any electrocardiographic ischaemic changes. No arrhythmias were noted on Holter monitor. Which of the following is most likely the diagnosis? Questions: A: Lateral and inferolateral myocardial infarction B: Congenital absence of pericardium C: Pseudoaneurysm D: Congenital left ventricular outpouching